Building Social Capital to Foster Interprofessional Education: The Interprofessional Educator Academy. (November 2019) - Lee, Linda S.; O'Connor Grochowski, Colleen; Valiga, Theresa M.; von Isenburg, Megan; Bures McNeill, Diana
Abstract : Interprofessional education (IPE) is promoted as a necessary precursor to the implementation of the collaborative practices in patient care thought to improve teamwork and communication among health care providers, patients, their families, and communities. Yet barriers to IPE persist, due largely to a lack of understanding on the part of health care team members about the norms and practices of health professions outside their own. A by-product of social interactions within groups and networks, social capital is a collective asset that contributes to the development of trust, innovation, and coordination of efforts toward mutual goals. Duke AHEAD (Academy for Health Professions Education and Academic Development), an interprofessional educator academy, is examined through the lens of social capital theory as a viable means of breaking down barriers to IPE, thereby improving patient care.